STUDENTS' UNDERSTANDING AND ATTITUDES TOWARDS SCHOOL-BASED MANAGEMENT FACULTY OF SCIENCE EDUCATION MAKASSAR STATE UNIVERSITY - Ermi Sola (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
This study aimed to determine whether there was a correlation between the level of students’ understanding of SBM (School Based Management) and students’ attitudes towards SBM in the Department of Educational Administration, Faculty of Education, Makassar State University. This research was a correlational research. The total population was 180 students and 42 of them were selected as samples taken through purposive random sampling technique. The research data were analyzed using Pearson Product Moment Correlation. The results showed that there was a significant correlation between students' understanding and their attitudes towards SBM. It can be concluded that the higher the level of students’ understanding of School Based Management, the more positive their attitude towards School Based Management.